Deteminant Organizational Development : Analysis Recruitment, and Servant Leadership - Indra Rustiawan; Lis Lesmini; Sonya Sidjabat; Sriwanti Belani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is that researchers want to provide an overview of whether there are research results from scientific articles related to research variables in the study, with the results of the analysis submitted then the researcher provides an answer in the form of perspective. The research method uses qualitative with literature review and From the results of the discussion above, researchers see from several variables in this study two variables, namely between recruitment and organizational development, were found significant from some existing article literature, the second between the variables of servant leadership on organization leadership does not state influence or is not directly affected, It's just a general discussion. In general, from this study, researchers see that it is still rare to discuss between the variables in this study and there are other variables that can be used as research gaps in the future.